Оценка эффективности управления организацией - Мусиенко, В. О. (ХНУРЕ, 2017)
The author has analyzed the methodological approaches to the assessment of the effectiveness of enterprise management. It is established that there is no common opinion as to the essence and evaluation of the company's management effectiveness. To date, in an unstable environment, taking into account the task of moving towards an innovative economy. Cost methods of assessing the effectiveness of the company's management while providing a balance of interests of all stakeholders are of interest.
Keywords: економічне моделювання; оценка эффективности управления; управление организацией